GERONTOLOGICAL TRAINING: THE CHALLENGE OF INTEGRATING DIFFERENT PROFESSIONAL CATEGORIES - Maria Angélica dos Santos Sanchez; Wallace Hetmanek dos Santos (Brazilian Society of Geriatrics and Gerontology, 2021)
Gerontological training must be present on the discussion agenda of several training and professional qualification entities. Despite the expressive increase in life expectancy in Brazil, the number of qualified professionals to adequately meet the demands of the aging population is below what is necessary in the country. While many countries are already organizing themselves to elaborate standards and guidelines for gerontological education, Brazil still moves slowly in the definition of professional competencies at different levels of education, hiding the visibility of the identity of professionals working in gerontology. This article aims to shed light on the topic of gerontological training based on joint efforts of scientific societies, professional councils, professional associations, and educational institutions.